2023
DOI: 10.1111/fare.12884
|View full text |Cite
|
Sign up to set email alerts
|

Navigating health and well‐being during the COVID‐19 pandemic: Experiences of Latina immigrant mothers in rural Midwestern communities

Abstract: ObjectiveIn this study, we sought to gain insight into the challenges Latina immigrant mothers in rural Midwest communities encountered during the pandemic, strategies they employed to avoid infection of the virus, and impacts of the pandemic on family health and well‐being.BackgroundIn rural Midwestern communities, the pandemic disproportionately affected immigrants, many of whom are Latino and worked in meatpacking and food processing plants. Latina mothers are commonly viewed as caretakers of the family. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Research with Latine mothers also supported the negative impact of the COVID-19 pandemic on their children. One study found that immigrant Latine mothers reported stress about meeting the basic needs of their families, such as ensuring their children had enough food and succeeded academically (Williams et al, 2023). Another study found that rural Latine immigrant mothers were less satisfied with communications from their children's schools and less likely to feel confident their children would be prepared for the next school year compared to urban mothers (Quandt et al, 2021).…”
Section: Mental Health In Latine Adolescents During the Covid-19 Pand...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research with Latine mothers also supported the negative impact of the COVID-19 pandemic on their children. One study found that immigrant Latine mothers reported stress about meeting the basic needs of their families, such as ensuring their children had enough food and succeeded academically (Williams et al, 2023). Another study found that rural Latine immigrant mothers were less satisfied with communications from their children's schools and less likely to feel confident their children would be prepared for the next school year compared to urban mothers (Quandt et al, 2021).…”
Section: Mental Health In Latine Adolescents During the Covid-19 Pand...mentioning
confidence: 99%
“…Rural communities were especially vulnerable to COVID‐19‐related economic shocks due to a heavy reliance on industries that are susceptible to pandemic‐related closures (e.g., factory work) as well as due to residing in communities of high levels of economic hardship and poverty. Latine immigrant workers in rural communities were often employed in occupations that were exempted from stay‐at‐home orders such as farm or agricultural work and meat and poultry processing, and many were ineligible for benefits such as unemployment (Quandt et al, 2021; Williams, et al, 2023). Compounding these experiences, many Latine immigrant families in new‐destination areas in the United States also experience additional stressors such as language barriers, geographic isolation, work‐related hazards, and poorer access to healthcare and other crucial services (Stein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%